Development of Drama Studies Teaching Material Based on 21st Century Skills and It for Students of Indonesian Language and Literature Education Study Program, Faculty of Language and Arts, Universitas Negeri Jakarta - Hestiyani Parai; Anastasya Wahyudanti Saputri; Lina Kartika Sari (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2022)
This research will develop a model of teaching materials for drama studies courses based on 21st century skills and ICT. The purpose of this research is to develop teaching materials for drama studies so that graduates of the Indonesian Language and Literature Education Study Program are able to understand drama study material according to the applicable curriculum and are able to implement it in schools. Preliminary research, first analyzing the need for teaching materials for drama studies courses for students. The results of this research are to develop and obtain teaching materials for drama studies based on 21st century skills and ICT for Indonesian language education study program students.